1989
DOI: 10.1007/bf01396364
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of the Gauss-Jordan algorithm

Abstract: Summary.In this paper a Gauss-Jordan algorithm with column interchanges is presented and analysed. We show that, in contrast with Gaussian elimination, the Gauss-Jordan algorithm has essentially differing properties when using column interchanges instead of row interchanges for improving the numerical stability. For solutions obtained by Gauss-Jordan with column interchanges, a more satisfactory bound for the residual norm can be given. The analysis gives theoretical evidence that the algorithm yields numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…If A is an n × n matrix, this pivoting strategy requires O(n 2 ) operations. Let us recall that in Reference [5] it was shown that GJE with this pivoting strategy presents a satisfactory bound for the residual norm, in contrast to the usual partial pivoting. Let us deÿne another pivoting strategy.…”
Section: Propositionmentioning
confidence: 97%
“…If A is an n × n matrix, this pivoting strategy requires O(n 2 ) operations. Let us recall that in Reference [5] it was shown that GJE with this pivoting strategy presents a satisfactory bound for the residual norm, in contrast to the usual partial pivoting. Let us deÿne another pivoting strategy.…”
Section: Propositionmentioning
confidence: 97%
“…The notion of equivalent perturbation (see [5]) is introduced for every piece of data (input, intermediate and output) in contrast to the Wilkinson's backward analysis, where equivalent perturbations of the inputs only are considered. Then a system of linear equations Be = ~7 (1) with respect to the vector of all the equivalent perturbations is derived. The solution of this system (if it exists) gives a first order approximation to the equivalent perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Email: walter@fwi.uva.nl pivoting strategy [6]. After the stability of GaussJordan's method had been properly established in 1989 [1], a stabilizing pivoting strategy for GaussHuard's method could be introduced. In 1992 it was proven that Gauss-Huard's method in combination with this pivoting strategy is numerically stable [3].…”
Section: Introductionmentioning
confidence: 99%